Odirecting Students to Creative Independent Activity Using Developing Technologies of Education (The Peerian Journal, 2023)
The article focuses on the orientation of students to creative independent activity, the development of independent labor creativity, cognitive activity, systemic thinking, which is important for the successful solution of life and professional tasks that young professionals may face.